Notch effect assessment in a PUR material using a ring shaped specimen. (October 2018) - Negru, R.; Serban, D.A.; Pop, C.; Marsavina, L.
Highlights: ASED method was employed to predict brittle failure of PUR porous material. Mode I, predominantly mode II and mixed mode loading conditions were produced using DCR specimen. The effect of notch radius was highlighted. Abstract: Notch effect in porous polyurethane rigid (PUR) materials is analyzed using a ring shaped specimen containing a single radially U-notch of different tip radii. If the specimen is subjected to a diametrically compressive load, various mixed mode I/II conditions are acquired depending on the notch orientation angle. A comparison between our experimental results and the theoretical predictions based on local strain energy density approach is presented. This criterion provides reasonable results for the final critical fracture load.